Stratosphere-troposphere coupling and its impacts on Northern winter subseasonal-to-seasonal forecast uncertainty ... - Späth, Jonas (Ludwig-Maximilians-Universität München, 2024)
Skill of mid-latitude weather predictions largely decays within the first two forecast weeks. Nonetheless, remote coupling with slower-evolving Earth system components can provide predictability beyond the local initial condition memory, at the so-called subseasonal-to-seasonal (S2S) timescale, which spans approximately from two weeks to two months. This thesis delves into a key source of S2S predictability for mid-latitude weather: stratosphere-troposphere coupling, specifically through the strong circumpolar winds in the Arctic stratosphere known as the polar vortex. Studies of stratosphere-troposphere coupling are often constrained by the scarcity of extreme events in observational records, especially for sudden stratospheric warmings (SSWs), which occur approximately once every second winter. Leveraging a large set of state-of-the-art S2S ensemble forecasts, this thesis improves the statistical characterization of SSWs by employing a sample size roughly 150 times larger than what is available from ... : Die Güte von Wettervorhersagen in den mittleren Breiten nimmt innerhalb der ersten beiden Vorhersagewochen stark ab. Dennoch kann eine gewisse Vorhersagbarkeit auch auf längeren Zeitskalen bestehen, wenn das Wettergeschehen mit sich langsamer verändernden Komponenten des Erdsystems gekoppelt ist. Diese Arbeit untersucht, wie solche Kopplungen zur Vorhersagbarkeit auf der subsaisonalen-bis-saisonalen (S2S) Zeitskala beitragen, was Vorhersagezeiten von etwa zwei Wochen bis zwei Monaten einschließt. Dabei liegt der Fokus auf einer der wichtigsten Quellen für S2S-Vorhersagbarkeit in den mittleren Breiten: der Kopplung zwischen Stratosphäre und Troposphäre, im Zusammenhang mit den starken zirkumpolaren Winden in der arktischen Stratosphäre, dem sogenannten Polarwirbel. Studien zur Stratosphäre-Troposphäre-Kopplung sind häufig dadurch limitiert, dass Extremereignisse in Beobachtungsdatensätzen nur selten auftreten. Dies trifft insbesondere auf plötzliche Stratosphärenerwärmungen (im Englischen “sudden ...